1998
DOI: 10.1037/0022-3514.75.2.332
|View full text |Cite
|
Sign up to set email alerts
|

The illusion of transparency: Biased assessments of others' ability to read one's emotional states.

Abstract: Three sets of studies provide evidence for an illusion of transparency, or a tendency for people to overestimate the extent to which others can discern their internal states. People often mistakenly believe that their internal states "leak out" more than they really do. The authors attribute this bias to a tendency for people to adjust insufficiently from the "anchor" of their own phenomenological experience when attempting to take another's perspective. Evidence for this illusion is provided by showing that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
332
2
3

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(353 citation statements)
references
References 49 publications
16
332
2
3
Order By: Relevance
“…Conceptually, this effect may reflect a special instance of a generalized, and perhaps motivated, belief in a just world in which human beings "get what they deserve" and "deserve what they get" (Lerner, 1980). The effect may also be viewed as symptomatic of an "illusion of transparency," a tendency for people to overestimate the extent to which their own thoughts, emotions, and other inner states are detectable and knowable by others (Gilovich, Savitsky, & Medvec, 1998;Miller & McFarland, 1987). This illusion was evident in a recent study in which mock suspects erroneously assumed that their guilt or innocence would be judged accurately by the interrogator-and by others who would observe their denials (Kassin & Fong, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, this effect may reflect a special instance of a generalized, and perhaps motivated, belief in a just world in which human beings "get what they deserve" and "deserve what they get" (Lerner, 1980). The effect may also be viewed as symptomatic of an "illusion of transparency," a tendency for people to overestimate the extent to which their own thoughts, emotions, and other inner states are detectable and knowable by others (Gilovich, Savitsky, & Medvec, 1998;Miller & McFarland, 1987). This illusion was evident in a recent study in which mock suspects erroneously assumed that their guilt or innocence would be judged accurately by the interrogator-and by others who would observe their denials (Kassin & Fong, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Innocence seems to be accompanied by a number of general beliefs and expectations. For example, it has been demonstrated that people believe that internal states leave visible traces on the outside (Gilovich, Savitsky, & Medvec, 1998;Savitsky & Gilovich, 2003;Vorauer & Claude, 1998). It may be that innocent suspects provide the truth without holding information back, because they believe that innocence is visible, and by acting in line with one's innocence, one will be judged correctly.…”
Section: The Phenomenology Of Innocencementioning
confidence: 99%
“…that holistically expressed person-object relations and perhaps included interjections to clarify such person-object relations (e.g., a prehistoric "oops" to indicate unintentionality or an ancient "there" to indicate intentionality; see Carpenter, Akhtar, & Tomasello, 1998). Add to that the fact that even in modern times communicators overestimate the clarity of their expressions and the transparency of their communicative intentions (Gilovich, Savitsky, & Medvec, 1998;Keysar, 1994). We can conclude, then, that protolanguage posed serious difficulties for the ancient social perceiver and may have caused a fair amount of misunderstanding and conflict within and between groups.…”
Section: Evolutionary Escalationmentioning
confidence: 99%